Case report: The role and value of radiotherapy in treatment of inflammatory myofibroblastic tumor - Guo, Haiwei; Jiang, Mingyun; Cai, Juanjuan; Liu, Ruiqi; Yao, Weiping; Liang, Xiaodong (Frontiers in Oncology, 2024)
BackgroundInflammatory myofibroblastic tumors (IMTs) are rare soft-tissue neoplasms. Accordingly, there is no standardized therapy for unresectable or advanced IMT. Chemotherapy, radiotherapy, and targeted molecular therapy play an important role in unresectable or advanced IMT.Case presentationWe present a 54-year-old man with a cough and chest distress case report. The thoracic surgeon performed the right upper pulmonary occupying lesion wedge resection and enlarged lymph node excision biopsy. Pathologic diagnosis revealed that the morphology of “right upper lung mass” was considered as Inflammatory Myofibroblastic Tumor (IMT). Radiotherapy was indicated at a high dose: 5400cGy in 27 fractions of 2Gy over 5 weeks were delivered combined with cisplatin. The patient was given a CT/MRI and hematological index every 3 months and experienced no more adverse events. The patient survives with no tumor recurrence as of the last follow-up. Progression-free survival (PFS) exceeded 5 years.ConclusionsWe have reviewed the literature and summarized and discussed the radiotherapy treatment options and challenges for IMT. We first reported high-dose radiotherapy combined with chemotherapy treatment for unresectable IMT. Concurrent radiochemotherapy may be considered an intensive treatment for local progress, local recurrence, and nonresectable IMT patients.